Lack of the COMPASS Component Ccl1 Reduces H3K4 Trimethylation Levels and Affects Transcription of Secondary Metabolite Genes in Two Plant–Pathogenic Fusarium Species - Studt, Lena; Janevska, Slavica; Arndt, Birgit; Boedi, Stefan; Sulyok, Michael; Humpf, Hans-Ulrich; Tudzynski, Bettina; Strauss, Joseph (Frontiers in Microbiology, 2017)
In the two fungal pathogens Fusarium fujikuroi and Fusarium graminearum, secondary metabolites (SMs) are fitness and virulence factors and there is compelling evidence that the coordination of SM gene expression is under epigenetic control. Here we characterized Ccl1, a subunit of the COMPASS complex responsible for methylating lysine 4 of histone H3 (H3K4me). We show that Ccl1 is not essential for viability but a regulator of genome-wide trimethylation of H3K4 (H3K4me3). Although recent work in Fusarium and Aspergillus spp. detected only sporadic H3K4 methylation at the majority of the SM gene clusters, we show here that SM profiles in CCL1 deletion mutants are strongly deviating from the wild type. Cross-complementation experiments indicate high functional conservation of Ccl1 as phenotypes of the respective ∆ccl1 were rescued in both fungi. Strikingly, biosynthesis of the species-specific virulence factors gibberellic acid and deoxynivalenol produced by F. fujikuroi and F. graminearum, respectively, was reduced in axenic cultures but virulence was not attenuated in these mutants, a phenotype which goes in line with restored virulence factor production levels in planta. This suggests that yet unknown plant-derived signals are able to compensate for Ccl1 function during pathogenesis.